A new duet in cancer biology: AMPK the typical and UBE2O the atypical. (4th May 2017) - Vila, Isabelle K.; Song, Su Jung; Song, Min Sup
ABSTRACT: Ubiquitin-conjugating enzyme E2O ( UBE2O ) is upregulated in human cancers. We have demonstrated that genetic deletion or pharmacological blockade of UBE2O reduces tumorigenesis through inhibiting the mammalian target of rapamycin complex 1–hypoxia-inducible factor 1-α pathway. Critically, UBE2O targets adenosine monophosphate (AMP)-activated protein kinase-α 2 (AMPKα2) for ubiquitination and degradation. We thus suggest the UBE2O-AMPKα2 axis as a potential therapeutic target for cancer.